To treat or not to treat? Adjuvant chemotherapy in 46 patients with stage IB lung squamous cell carcinoma: a real-world matched analysis - Liang, Botao; Fu, Tingting; Guo, Juntang; Zhang, Lianbin; Liang, Chaoyang; Zhang, Tao; Zhao, Kai; Gao, Zhaofeng; Yang, Jing; Shen, Leilei (Frontiers in Oncology, 2025)
BackgroundThe value of adjuvant platinum-based chemotherapy (ACT) in stage IB squamous cell carcinoma (SqCC) remains controversial.MethodsThis retrospective study enrolled patients with surgically resected stage IB SqCC between January 2013 and August 2024. Clinicopathological characteristics and survival data were collected. To mitigate the impact of observed confounders, propensity score matching (PSM) was performed using clinically relevant covariates, including age, sex, tumor diameter, poor differentiation, spread through air spaces, visceral pleural invasion, and lymphovascular invasion, resulting in 46 well-matched patient pairs. The primary endpoint was disease-free survival (DFS). The secondary endpoint was overall survival (OS).ResultsA total of 181 patients were enrolled in the study. Among them, 50 patients (27.6%) received adjuvant chemotherapy (ACT), while 131 patients (72.4%) were assigned to the clinical observation (CO) group. The ACT group had more patients <65 years (P = 0.007), larger tumors (P < 0.001), and more poorly differentiated tumors (P = 0.017) compared with the CO group. The two groups were comparable after PSM. Among the ACT group, twenty-eight (56%) patients received cisplatin plus docetaxel regimen. 16% (8/50) of patients took cisplatin plus gemcitabine regimen, and carboplatin plus paclitaxel was 14 (28%) patients’ option. The median follow-up time was 60 months (range: 5–137 months). The 5-year DFS rates were 84.8% in the ACT group and 85.6% in the CO group (HR: 1.05, 95% CI 0.44-2.51; P = 0.919). There was no statistically significant difference in DFS between groups, both in the entire cohort (P = 0.701) and the matched cohort (P = 0.665). The 5-year OS rates were 96.8% in the ACT group and 93.1% in the CO group (HR: 2.46, 95% CI 0.72-8.35; P = 0.150). No statistically significant difference in OS was observed, either in the overall cohort (P = 0.131) or in the matched cohort (P = 0.300).ConclusionsACT may not confer significant survival benefits in resected stage IB SqCC, with comparable disease-free and overall survival outcomes observed between treatment and observation groups.